Impact of salicylic acid on wheat growth and nutrient uptake in salinized environments - Anjum, Muhammad Ashfaq; Sarfraz, Muhammad; Qureshi, Muhammad Amjad; Rizwan, Muhammad; Naz, Asifa; Ahmed, Khalil; Saqib, Amar Iqbal; Nawaz, Muhammad Faisal; Nawaz, Muhammad Qaisar; Ali, Muhammad Asif; Khalid, Muhammad; Shabbir, Ghulam; et al. (Journal of Pure and Applied Agriculture, 2023)
Field study was performed to explore the salicylic acid (SA) impact applied as priming agent and as foliar spray on wheat growth, yield and nutrient uptake in saline sodic conditions. Soil sampling of the selected field was carried out and composite soil samples were analyzed for salinity and fertility status of soil. The priming of wheat seeds (cv. Inqlab-91) was carried out by soaking 500g of seeds in 1000 mL solution of SA having 0.5, 1.0 and 2.0 mM concentrations for 12 hours. The primed wheat seeds were dried under shade. After the booting stage, 03 foliar sprays of given concentrations were carried out at a 10 days interval. The control was without priming SA and applied only recommended fertilizer @ 120-90-70 kg N-P-K ha-1, respectively. The set of treatments replicated thrice following RCBD. Results revealed that the combination of priming and foliar spray of SA affected the wheat yield components, N-P-K uptake significantly. The highest wheat biomass, grain and straw yield, N-P-K content and uptake were observed at 2.0 mM SA with priming and foliar spray and statistically insignificant to SA at 1.0 mM. The minimum values of yield components and nutrient content and uptake were found in control. At harvest, soil fertility status was quite improved and slight reduction in the salinity/sodicity parameters was observed with SA application.